Influence of Ethnicity, Gender and Answering Mode on a Virtual Point-to-Origin Task - Kitson, Alexandra; Sproll, Daniel; Riecke, Bernhard E. (Frontiers in Behavioral Neuroscience, 2016)
In a virtual point-to-origin task, participants seem to show different response patterns and underlying strategies for orientation, such as ”turner” and ”non-turner” response patterns. Turners respond as if succeeding to update simulated heading changes, and non-turners respond as if failing to update their heading, resulting in left-right hemisphere errors. We present two other response patterns, ”non-movers” and ”spinners”, that also appear to result in failures to update heading. We have three specific goals in mind: (1) extend previous findings of higher turner rates with spatial language response mode using a point-to-origin task instead of a triangle completion task; (2) replicate the gender effect of males more likely responding as turners; (3) examine ethnicity influence. Designed as a classroom study, we presented participants (N = 498) with four passages through a virtual star field. Participants selected the direction pointing to the origin from four multiple-choice items. Response mode was either pictograms or written lan- guage, chosen to compare with similar studies and see if these response modes have an effect on virtual orientation behaviour. Results show a majority of participants (48.35%) classified as non-turners, 32.93% turners, 15.57% as non-movers, and 3.14% as spinners. A multinomial regression model reached 49% classification performance. Written spatial language, compared to pictograms, made turner response patterns more likely; this effect was more pronounced for Chinese participants and among females, but not male Caucasians. Moreover, higher turner numbers for written spatial language extends Avraamides findings of higher turner numbers when participants turned their bodies toward the origin but not when they responded verbally. Using pictorial response mode (i.e., top-down picture of a head) may have increased cognitive load because it could be considered more embodied. It remains to be seen how we can reduce the reference frame conflict that might have caused increased cognitive load. Second, our results are inconsistent with previous research in that males overall did not show more turner behaviour than females. Future research may look at possible underlying factors, such as cultural norms. Third, individualistic cultures (Caucasians) [Greif, 1994] lean towards turner response patterns, whereas collectivist cultures lean towards non-turner response patterns.